Análisis de los posibles efectos de la aplicación de la NIIF en la presentación del Balance General en Colombia (2014)
Currently in the commercial sector Colombian companies present their financial statements in accordance with Decree 2649 of 1993 arising from the Act 43 of 1990, this decree does not take into account the changes suggested in 2009 under Law 1314, which generates standard expansion accounting standards towards homogenization with international guidelines; for this is considered an important issue an analysis of the possible effects of the implementation of IFRS in the presentation of the Balance General; due to the importance of the subject and creates the impact that a change of this size conceived in the organization.